2018
DOI: 10.1159/000494280
|View full text |Cite
|
Sign up to set email alerts
|

Spigelian Hernia: Case Series and Review of the Literature

Abstract: Background: Spigelian hernia (SH) is an uncommon ventral abdominal hernia. Traditionally repaired with an open technique, the laparoscopic approach is becoming more common and widely described in the literature. We hold that the transabdominal preperitoneal (TAPP) approach restores the anatomy and prevents complications such as seroma. We present a series of SH repair carried out at a single district general hospital over the past 13 years and a review of the literature. Methods: A retrospective case note revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 17 publications
2
35
1
4
Order By: Relevance
“…The hernial sac is typically intraparietal, passing through the transversus and internal oblique aponeuroses and extending out beneath the external oblique or within the rectus sheath [1]. The reported literature shows that hernia usually consists of preperitoneal fat [6]. However, the hernia may contain small bowel, colon, omentum, or occasionally, the appendix [7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hernial sac is typically intraparietal, passing through the transversus and internal oblique aponeuroses and extending out beneath the external oblique or within the rectus sheath [1]. The reported literature shows that hernia usually consists of preperitoneal fat [6]. However, the hernia may contain small bowel, colon, omentum, or occasionally, the appendix [7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Most authors suggest repairing the Spigelian hernia as the fascia here typically forms a rigid neck which could lead to future incarceration or strangulation. The reported incidence of incarceration is between 24% -27% and strangulation at 2% -14% [6].…”
Section: Discussionmentioning
confidence: 99%
“…Spigelian hernia occurs due to a weakness of the spigelian fascia, which is the layer between rectus muscle and semilunar line [3]. The absence of a posterior rectus sheath is a contributing factor at this location and therefore mostly occurs below the arcuate line.…”
Section: Spigelian Herniamentioning
confidence: 99%
“…A MEDLİNE search of the published literature shown that 232 cases in which the results of SH patients operated between 1997 and 2017 were evaluated; the most common choice was IPOM 32%, TEP 30%, and TAPP 22%. In laparoscopic mesh repair, onlay mesh, mesh extended to the retrorectus cavity, mesh repair placed in the extraperitoneal space were defined at the largest case series of 107 cases of laparoscopic repair which was published by Weber et al [17]. The risk of neurovascular injury in the posterolateral abdominal wall due to the tacker usage for abdominal wall fixation of these meshes is reported to be higher in IPOM and TAPP operations.…”
Section: Surgical Indicationmentioning
confidence: 99%